The Mediating Roles of Future Work Self and Hope on the Association Between Perceived Social Support and Depressive Symptoms Among Chinese Vocational School Students: A Cross-Sectional Study - He Y; Zeng Q; Zhang M (Psychology Research and Behavior Management, 2023)
Yingshi He,1,* Qing Zeng,1,* Minqiang Zhang1– 4 1School of Psychology, South China Normal University, Guangzhou, People’s Republic of China; 2Key Laboratory of Brain, Cognition and Education Sciences, Ministry of Education, Guangzhou, People’s Republic of China; 3Center for Studies of Psychological Application, School of Psychology, Guangzhou, People’s Republic of China; 4Guangdong Key Laboratory of Mental Health and Cognitive Science, South China Normal University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Minqiang Zhang, School of Psychology, South China Normal University, No. 55, West of Zhongshan Avenue, Tianhe District, Guangzhou, 510631, People’s Republic of China, Email 2640726401@qq.comPurpose: Depressive symptoms are serious mental health problems, which are harmful for adolescents’ physical and psychological development. Limited studies have focused on depressive symptoms of vocational high school students, who are more susceptible to mental health problems than high school students. Based on the main effect model of social support and self-regulation theory, the current study aims at exploring two potential mediating roles of hope and future work self on the relationship between perceived social support and depressive symptoms among vocational high school students by a cross-sectional study.Participants and Methods: A total of 521 vocational high school students aged 14– 21 (M= 16.45; SD= 0.91) participated in the survey. There were 266 males (51.1%) and 255 females (48.9%). The multidimensional scale of perceived social support, the future work self scale, the children’s hope scale, and the center for epidemiologic studies depression scale were applied in the study.Results: The results revealed that: (1) perceived social support, future work self, and hope were negatively related to depressive symptoms (r = − 0.25 to − 0.35, p < 0.001); (2) students who perceived more social support have fewer depressive symptoms (β = − 0.22, p < 0.001); (3) perceived social support predicted a more salient future work self and then was associated with higher levels of hope, which in turn, was related to lower levels of depressive symptoms (β = − 0.02, and 95% CI = [− 0.035, − 0.005]).Conclusion: Perceived social support was the protective factor against vocational school students’ depressive symptoms. More specifically, stronger perceived social support predicted a more salient future work self, which promoted high level of hope, and ultimately decreased vocational school students’ depressive symptoms. The findings provide enlighten implications for interventions on depressive symptoms among vocational high school students.Keywords: perceived social support, future work self, hope, depressive symptoms, vocational high school students